Participating in the world: select American press coverage of United States internationalism, 1918-1923 - Pituch, William G. (Kansas State University, 2008)
This thesis examines the internationalist message in news coverage and editorial commentary of a select group of American newspapers in the last throes and years immediately after World War I. Some historians have misinterpreted this period as a "return" to isolationist sentiments throughout America. However, the articles and editorials in these papers presented a message that America was still concerned with the happenings of the world and willing to participate in ascertaining solutions to the problems confronting Europeans as well as other peoples around the globe. The first chapter looks at the late stages of the war through the Senate's rejection of the Versailles Treaty. These papers initially presented a message of hope that the war could become the last war in history, spearheaded by President Wilson's Fourteen Point program. However, these hopes were dashed when the Fourteen Points were largely overlooked in the treaty. In the ensuing fight between the administration and the treaty's dissenters there were no threats of isolating the country from world affairs. According to these sources, those proposing reservations to the treaty were unwilling to commit the country to the League of Nations because they believed the League to be a permanent military alliance that violated the Constitution. The second chapter examines how the debate over the treaty and League membership became significant issues throughout 1920, reaching a climax with the presidential election in November. This section focuses on the coverage of Senator Harding's message of continued U.S. international participation throughout the campaign. The coverage from these papers regarding the international affairs of and events during the Harding administration is investigated in the final chapter. This chapter focuses heavily on the reactions to the Washington Conference of 1921-1922 which established international naval arms limitations. Harding and his policies enjoyed significant popular support from many of these papers because they believed he established a lasting peace. Throughout this period, the editorials and news coverage in these papers presented U.S. leaders as actively participating in global affairs rather than proposing the country step back from a leadership position in the world.
Keywords: Wilson, Woodrow; American newspapers; Harding, Warren; 1920 election; World War one America; Taft, William Howard; History, United States (0337); Political Science, General (0615); Political Science, International Law and Relations (0616)